Impact of Rain Water Infiltration on the Stability of Earth Slopes - Muhammad Farooq Ahmed; Xin Kang; Muhammad Saleem Khan (International Journal of Economic and Environmental Geology, 2016)
Slope failure occurs very often in natural and man-made slopes which are subjected to frequent changes in ground water level, rapid drawdown, rainfall and earthquakes. The current study discusses the significance of water infiltration, pore water pressure and degree of saturation that affect the stability of earth slopes. Rainwater infiltration not only mechanically reduces the shear strength of a slope material, but also chemically alters the mineral composition of the soil matrix. It results in the alteration of macro structures which in turn decreases the factor of safety. A few case studies are discussed in this paper to quantitatively observe the variation in factor of safety (FOS) of various earth slopes by changing the degree of saturation. The results showed that most of the earth slopes get failed or become critical when the degree of saturation approaches to 50 % or more. Keywords: Seepage, slope failure, infiltration, factor of safety, unsaturated soil